Santri Besek alias James Bond: Unveiling communication dynamics in mosque life - Anang Masduki; Prayudha Prayudha; Panqiang Niu (Asosiasi Pendidikan Tinggi Ilmu Komunikasi (ASPIKOM), 2024)
Santri Besek or James Bond is the term for the residents of the mosque in Yogyakarta. This research aims to reveal, first, the background and motivation of Santri Besek or James Bond to become a mosque caretaker. Second, it tries to reveal the intricacies of the sociology of communication that occurs between Santri Besek, also known as James Bond, and the principle of religious values within the community. Third, how the discourse process and dialectics in it. This type of research is descriptive qualitative, with phenomenological method. The theoretical framework used is symbolic interactionism theory. Data collection techniques with in-depth interviews with purposive sampling techniques. The interviewees were the perpetrators of Santri Besek or James Bond, community leaders, and taker administrators, totalling 30 people. Then, the results of documentation and observation data. Various kinds of data were then analysed using phenomenological methods. The study results found that economic problems and a high determination to achieve education became the background for them to become James Bond or Santri Besek. Then, several phrases were found in social interactions between mosque residents and the community. Such as santri besek or James Bond, ngriwek, boso walikan. Behind these phrases are pejorative sentences. The word santri besek is a mockery to emphasise the status of the mosque caretaker who is poor and becomes a prayer worker.